(untitled) - Raková, Zuzana (Romanica Olomucensia, 2011)
Frankofile and francophone elite of the Czech society has played since the 19th century an important role in mediating the Czech-French relationships. On the example of two importants translators, Jaroslav Vrchlický and Hanuš Jelínek and their contemporaries, the paper follows the birth of Czech French-speaking cultural and political elite from the 70s of the 19th century to 1918.
Keywords: francophony; francophilie; Czech translators; Czech elite.